2020
DOI: 10.3233/atde200204
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Framework Enabling Organizational Digital Readiness

Abstract: Digitalization and the use of advanced technologies for more flexible and resource efficient production processes are changing the industrial competitive environment. However, new technologies are not seldom implemented without the whole organization being ready to fully utilize its benefits. This readiness can be expressed as organizational digital maturity. Previous studies identified that the level of digitalization is increasing, but, in many cases, due to lack of foundation, it is not aligned with the bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The different aspects included in the set of readiness conditions were deployed into 50 questions, tested in a study conducted at one of the units of LC3 and reported by Machado et al (2020). After this initial study, the set of questions were reviewed, and a workshop was planned with a group of practitioners (managers, engineers and supervisors from different business units and areas) responsible for developing the LC3's global program for digital transformation.…”
Section: Methodsmentioning
confidence: 99%
“…The different aspects included in the set of readiness conditions were deployed into 50 questions, tested in a study conducted at one of the units of LC3 and reported by Machado et al (2020). After this initial study, the set of questions were reviewed, and a workshop was planned with a group of practitioners (managers, engineers and supervisors from different business units and areas) responsible for developing the LC3's global program for digital transformation.…”
Section: Methodsmentioning
confidence: 99%
“…Next, there is no specific tool to measure/assess the readiness of disaster management agencies on the application of IR4.0 technologies for Sarawak Disaster Management Agencies (SDMAs). Machado et al (2020) have discovered that it is crucial to create a proper readiness framework to ensure that its digital maturity has evolved [39]. According to Schumacher et al ( 2016), readiness assessments are used before the maturing process, whereas maturity assessments are used to capture the current condition during the maturing process [40].…”
Section: Research Problemmentioning
confidence: 99%
“…According to Schumacher et al ( 2016), readiness assessments are used before the maturing process, whereas maturity assessments are used to capture the current condition during the maturing process [40]. In order for digital transformation to be successful, an organisation's readiness for change must be demonstrated [39]. Hence, creating a roadmap for organisational readiness for digital transformation begins with an evaluation of the company's current digital situation and capabilities and a determination of where technological and organisational adjustments are required [41].…”
Section: Research Problemmentioning
confidence: 99%
See 2 more Smart Citations